Junctional kyphosis: how can we detect and monitor it during growth?. Issue 2 (October 2016) - Negrini, Alessandra; Donzelli, Sabrina; Maserati, Laura; Zaina, Fabio; Villafañe, Jorge; Negrini, Stefano
Abstract Background Despite its importance in affecting adult pain, and disability, there is a lack of universal criteria for the diagnosis and evaluation of thoraco-lumbar Junctional Kyphosis (JK) and a gold standard measurement and diagnostic system does not exist. This study aims to verify the sensibility and specificity of clinical, and Formetric surface topography (FST) data in identifying Junctional Kyphosis in respect to the radiographical standard references. Methods Design: This is a cross sectional study from a prospective database started in March 2003. Participants: 38 subjects. Inclusion criteria: Patients selected by age according to Risser score 1, at first visit with lateral x-rays and FST. Diagnostic test used to detect JK:FST criteria: level of thoraco-lumbar inflexion point in percentage compared to the total height of the spine. X-ray criteria: lower limit of thoracic kyphosis below T12. Statistics: sensitivity, specificity, positive (PPV) and negative predictive values (NPV), ROC curve. Results FST showed a good reliability in detecting JK: with a threshold of 75 %, PPV was 100 %, NPV was 86 % and the Area Under the Curve was 83 %. Conclusion The need for a useful criteria able to characterize JK to allow diagnosis and monitoring of the deformity is still lacking, and further studies will deepen this issue.